RAGE is a critical factor of sex-based differences in age-induced kidney damage - Bajwa, Seerat; Luebbe, Alexander; Vo, Ngoc Dong Nhi; Piskor, Eva-Maria; Kosan, Christian; Wolf, Gunter; Loeffler, Ivonne (Frontiers in Physiology, 2023)
Advanced glycation end-products (AGEs) are a heterogeneous group of molecules with potential pathophysiological effects on the kidney. Fibrosis together with accumulation of AGEs has been investigated for their contribution to age-related decline in renal function. AGEs mediate their effects in large part through their interactions with RAGE (receptor for AGEs). RAGE is a transmembrane protein that belongs to the immunoglobulin superfamily and has the ability to interact with multiple pro-inflammatory/pro-oxidative ligands. Role of RAGE in aging kidney has not been fully characterized, especially for sex-based differences. Therefore we analyzed constitutive RAGE knockout (KO) mice in an age- and sex-dependent manner. Paraffin embedded kidney sections were used for histological analysis and protein expression of fibrosis and damage marker. RNA expression analysis from kidney cortex was done by qPCR for AGE receptors, kidney damage and early inflammation / fibrosis factors. FACS analysis was used for immune cell profiling of kidney. Histological analysis revealed enhanced infiltration of immune cells, (positive for B220) in old (>70 weeks old) KO in both sexes. FACS analysis revealed similar pattern of enhanced B-1a cells in aged KO mice. There was an aged based increase in pro-fibrotic and pro-inflammatory markers (IL-6, TNF, TGF-β1 and SNAIL1) in KO males that presumably contributed to renal fibrosis and renal damage (glomerular and tubular). In fact, in KO mice there was an age-dependent increase in renal damage (assessed by NGAL, KIM1) that was accompanied by increased fibrosis (assessed by CTGF). This effect was more pronounced in male KO mice compared with female animals. In contrast to the KO animals, no significant increase in damage markers was detectable in the wildtype animals at the age examined (>70 weeks old). Moreover there is an age-based increase in AGEs and scavenger receptor MSR-A2 in kidney. Our data suggests that loss of the clearance receptor RAGE in male animals further accelerates age-dependent renal damage; this could be in part due to increase AGEs load in aging, and absence of protective female hormone. In females on contrast RAGE expression seems to play only a minor role to the tissue pathology.